The Evolution of Annual Immunization Recommendations Against Influenza in Italy: The Path to Precision Vaccination - Sara Boccalini; Chiara de Waure; Linda Martorella; Paolo Orlando; Paolo Bonanni; Angela Bechini (Vaccines)
Influenza vaccination is the health intervention that best guarantees protection against seasonal influenza. Every year, the Ministry of Health issues a document (namely a circular) containing recommendations for the use of available vaccines to prevent and control influenza. A review of the Ministerial Circulars released by the Italian Ministry of Health was conducted with the aim of assessing the evolution over time of the vaccination target recipients, the vaccines that can be used in the following influenza season, and the indications of use for age and appropriateness. Changes have emerged regarding these issues. In fact, over time, the vaccination offer has been extended to children between 6 months and 6 years of age, to adults aged 60–64 years, and to women in any trimester of pregnancy and postpartum. In parallel, from the 2018–2019 season, following the availability of new vaccines, the concept of vaccine appropriateness was introduced to the recommendations, i.e., the choice of the most appropriate vaccine for each subject to be vaccinated. The last circulars introduced the indication of the type of vaccine that can be administered for each target category and the recommendation to use adjuvanted and high-dose vaccines for adults aged ≥ 65 years. The annual recommendations provided by the Italian Ministry of Health, resultantly, are increasingly precise, emphasizing the importance of the concept of appropriateness and outlining the path to precision vaccination. To achieve maximum value in terms of clinical efficacy and community benefits, this concept should continue to be considered as a basis for the development of future recommendations, as it addresses a critical public health issue related to vaccination.